Local‐time‐dependent low‐altitude ion spectra deduced from TWINS ENA images. Issue 6 (3rd June 2013) - Goldstein, J.; McComas, D. J.; Valek, P.; Redfern, J.; Søraas, F.; Bazell, D.
Abstract : [1] In this paper, we analyze Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) stereo observations of energetic neutral atoms (ENAs) produced from the low altitude emission (LAE) region during the interval 1130–1146 UT on 6 April 2010. Geometrical calculations determine the geophysical locations of pixels at or near the LAE limb and the associated uncertainties. For our event, the two TWINS imagers observed a broad (8.4–9.2 h wide in magnetic local time (MLT)) region of LAEs on the opposing limb, possibly containing an ion boundary near dusk. The most intense LAEs were detected in a narrow range of magnetic latitude (67°–74°) and pitch angle (112°–116°). We implement a simplified thick‐target approximation (TTA) to obtain ion spectra from TWINS LAEs and perform a validation study using a conjunction of the TWINS‐observed LAE crescents with a simultaneous NOAA 17 polar‐orbit pass slightly west of the TWINS LAEs. Since TTA is limited to the brightest portion of LAEs, we apply our analysis for pixels with at least 30% of the peak value. TWINS ion spectra are calculated for individual pixels spanning several hours of MLT. The spectra exhibit a pronounced local time dependence. For more westward MLT (and more equatorward latitude), there is a shift toward spectra that are more energetic and peaked. This spatial dependence is consistent with ion drift theory and previous observations. The peaked LAE‐derived ion spectra of 6 April 2010 are notably different than those observed during much weaker disturbances, but are consistent with LAE observations from similar activity levels. These results demonstrate that with proper caution in interpreting the results, TWINS ENA imaging resolves MLT‐dependent (and to a limited extent, latitude‐dependent) low‐altitude ion spectral shape information, simultaneously across a broad range of MLT. This study advances previous results that considered much coarser MLT structure in LAEs and augments previous statistical spectral analysis of in situ data. Key Points: TWINS low‐altitude ion spectra are calculated at several hours of nightside MLT. More westward and equatorward spectra are more energetic, and peaked. ENA imaging resolves the MLT‐dependence of low altitude spectral shapes.